Sistem Kepartaian di Amerika Serikat dan Indonesia: Sebuah Studi Komparasi Politik - Imron Wasi (Jurnal Silatene Sosial Humaniora, 2025)
The party systems of the United States and Indonesia exhibit significant differences. However, both countries implement a presidential system of government and are also democratic. These differences in party systems can explicitly influence political systems, such as decision-making. In the Indonesian context, with its multi-party system, it is difficult for members and cadres of political parties in the legislature or parliament to secure political support for the government. This has implications for the formation of coalitions by the executive branch before competing in the electoral process. In contrast, in the United States, only two political parties represent the ideology of its people. This research method uses a qualitative descriptive approach with a preference-based approach, including sources such as scientific journals, books, research reports, and relevant research reports (Zed 2004). Furthermore, in analyzing the research object, the author uses the perspective presented by Heywood (2014) because it is relevant to the research object. Consequently, the multi-party system implemented in Indonesia, coupled with the presidential system, results in executive leaders building political alliances before the political arena begins. This is done to gain political support in parliament. There are only 580 seats available. In other words, it seems difficult for any candidate party running in the election to win the most votes. Deadlocked policies and programs are likely to occur if executive leaders lack parliamentary support, resulting in faltering political decisions. Meanwhile, the United States tends to be more stable, as there are only two political parties representing their respective ideologies. Nevertheless, political dynamics in the United States often give rise to their own dynamics.